Safety of the Polish BCG-10 Vaccine During a Period of BCG Vaccine Shortage: An Australian Experience. Issue 6 (June 2020) - Wong, Nicole X.; Buttery, Jim; McMinn, Alissa; Azhar, Zainul; Crawford, Nigel W.
Abstract : Bacille Calmete-Guerin vaccine is widely administered to reduce the risk of severe tuberculosis disease in children. Recent global vaccine supply issues have led to the use of alternative products, which may vary in side effect profile. We report on the safety of the Polish (Moreau strain) "Bacille Calmete-Guerin-10" vaccine in an Australian cohort. Using active surveillance, we identified an adverse event rate of 54.6 per 10, 000 doses (95% confidence interval: 38.5–75.2), which was comparable to that reported with the Danish Sanofi-Pasteur and Connaught strains.